Microbial feedbacks on soil organic matter dynamics underlying the legacy effect of diversified cropping systems. (April 2022) - Mooshammer, Maria; Grandy, A. Stuart; Calderón, Francisco; Culman, Steve; Deen, Bill; Drijber, Rhae A.; Dunfield, Kari; Jin, Virginia L.; Lehman, R. Michael; Osborne, Shannon L.; Schmer, Marty; Bowles, Timothy M.
Abstract: Crop rotations have well-known aboveground and belowground benefits. At regional to continental scales, the unifying mechanisms of how diversified rotations alter soil organic matter (SOM) dynamics have not been demonstrated. We assessed how increasing crop rotational diversity across a soil-climate gradient affected the integrated response of SOM chemistry, microbial community composition, and its enzymatic potential to degrade SOM. Agroecosystems with the same crop rotational diversity (all sampled during the corn phase) shared similarities in molecular SOM patterns with a strong microbial signature, pointing to common transformation processes. Differences in SOM chemistry between rotations were mainly characterized by shifts in microbial necromass markers and in lipids produced or transformed by microbes rather than by intact plant lipids. Microbial resource allocation to enzymes, which catalyze the decomposition of organic matter, differed between systems. Lower resource investment into recalcitrant C-degrading enzymes with increasing crop diversity indicates higher resource availability for the microbial community. Our multivariate analyses suggest that this could be regulated via relative changes in microbial functional groups – emergence of relatively more non-oxidase producing microorganisms like arbuscular mycorrhizal fungi rather than an absolute decrease in oxidase producing microbes. These uniform responses to increased crop rotational diversity over a wide geographical area point to enhanced stabilization of microbial-derived SOM and functional shifts in the microbial community as a common mechanism underlying the positive plant-soil feedback in diversified cropping systems. Highlights: We found uniform soil responses to higher crop diversity over a wide geographical area. Crop rotations shared similarities in SOM chemistry with a strong microbial signature. Increased crop rotational diversity led to distinct microbial communities. With diverse rotations, soil microbes invested in fewer recalcitrant C-degrading enzymes.